PENINGKATAN KETERAMPILAN MENYIMAK TEKS NARASI MENGGUNAKAN TEKNIK 5W+1H PADA SISWA KELAS VII D MTS NEGERI 2 PONTIANAK - Widya Viantini; Nanang Heryana; Syambasril Syambasril (Universitas Tanjungpura, 2019)
AbstractNarrative text is one of the competencies that must be mastered by students in writing learning, in which there are elements such as themes, characters, backgrounds, lines, and mandates.The results of the pre-observation in class VII students at Pontianak State 2 MTs showed that in class VII D there were still students who did not listen well to the subject matter of the narrative text delivered by Indonesian language teachers, the research problem raised was “ how the skill improvement of listening to narrative texts using the 5W+1H technique in class VII students of MTs negeri 2 Pontianak”?. The method used in this study is the action research method. The form of research in this paper is classroom action research (CAR). .the results of this study were: 1) the process of using the 5W+1H technique in improming the skills of listening to narrative tekts ini class VII D students of MTs NEGERI 2 PONTIANAK in the first cycle wa classified ad good and in the second cycle was very good: 2) the results of the ability to lisen to nararative texts using the 5W+1H technique in students of class VII D MTs Negeri 2 Pontianak show high scores and above the KKM. Keywords: Improvement, skills, listening, text narration, 5W+1H technique